Effect of silane coupling agents on properties and performance of polycarbonate/silica MMMs - Idris, A. (2019)
The choice of amine terminated silanes remain scarce although they have been used as coupling agents to enhance silica dispersion and interaction in polymer matrix. Functionalized silica particles were synthesized by co-condensing tetraethyl-orthosilicate with four types of silane agents in sol-gel process. These particles were characterized and incorporated into polycarbonate polymer matrix. The morphology, structure, thermal stability, mechanical strength and gas (N2, CH4, CO2) permeation properties of mixed matrix membranes (MMMs) were characterized by standard techniques. The functionalized silica particles were of various particle sizes and extent of functionalization. PC/Silica MMM produced by incorporating functionalized silica particles using (3-aminopropyl) trimethoxysilane exhibited better morphology. The corresponding MMM performance has improved (Î±CO2/N2 = 42.8 and Î±CO2/CH4 = 38) as compared to pure PC membrane (Î±CO2/N2 = 20.30 and Î±CO2/CH4 = 18.5) and other MMMs. Thus, low molecular weight single amine terminated silane agents are potential candidates for the development of PC/silica MMMs. Â© 2018 Elsevier Ltd